2009
DOI: 10.1080/13625180802512994
|View full text |Cite
|
Sign up to set email alerts
|

Impact of post-abortion family planning services on contraceptive use and abortion rate among young women in China: a cluster randomised trial

Abstract: Couples who received the comprehensive post-abortion FP service appear to use more effective contraceptive methods and show better compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(87 citation statements)
references
References 15 publications
1
84
0
1
Order By: Relevance
“…Four of the studies took place in developed countries: Iceland,20 Italy,17 Scotland19 and the USA 22. The remaining two studies were carried out in newly industrialised countries: China21 and Brazil 18…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four of the studies took place in developed countries: Iceland,20 Italy,17 Scotland19 and the USA 22. The remaining two studies were carried out in newly industrialised countries: China21 and Brazil 18…”
Section: Resultsmentioning
confidence: 99%
“…and Langston et al 22. both only included participants that were over 18 years of age, whereas Zhu et al 21. reported that all participants were under the age of 25 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study from China compared the use of 2 contraceptive packages (one comprising limited information, the other providing more extensive information and including free contraceptives and partner involvement) among young women [19]. Both packages led to increased use of contraceptive methods but the extensive package also increased the use of more effective methods [19].…”
Section: Discussionmentioning
confidence: 98%